Automated Examination Timetabling System (AETSys) / Ariff Md Ab Malik - Md Ab Malik, Ariff; Haruddin, Hanitahaiza; Alwi, Anisah; Mohamed, Khainizam (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
This system is an examination timetabling automated generator that uses to construct a feasible and optimized university examination timetable. Depending on the student-exam population size, this system can produce a timetable within a short period of time. The main objective of this system is to automate the process of examination timetable construction which can be considered as difficult and time-taking process. This system has been developed based on a hybridization of local search-population based metaheuristic algorithms. The whole process of timetable construction can be divided into two major phases; (i) timetable development and (ii) timetable optimization. The Graph Colouring technique is used for the first phase of the process and meanwhile the metaheuristic technique will be applied in the second phase process. The main core of the technique of this system is Tabu Search algorithms that have been applied with several state-of-the-art strategies such as adaptive switcher mechanism and stratified descent selection mechanism. This technique was tested on the benchmark datasets and had produced some significant results against other reported state-of-the art techniques.